Solving some nonlinear equations by successive approximations - Albert K. Kalinde (International Journal of Mathematics and Mathematical Sciences, 2002)
The iterations scheme generated by an infinite sequence of operators satisfying some contractive conditions in a complete metric space is used to solve some integral equations of Hammerstein type.